1999
DOI: 10.1002/chin.199902190
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Diterpenoids from the Japanese Liverwort Jungermannia infusca.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Purification and structural characterization of both compounds by NMR (Figs S20 – S23 and Tables S6 & S7) revealed that SsSS removes the diphosphate and forms a tertiary alcohol, ent -kolavelool ( 35 )(Soares et al, 2014), while KgTS removes the diphosphate and forms an additional carbon-carbon double bond, producing the exo -methylene containing (5 R ,8 R ,9 S ,10 R )-cleroda-3,13(16),14-triene ( 36 ), which has been previously observed (Nagashima et al, 1998). Notably, SsSS and KgTS also readily react with kolavenyl diphosphate ( 13 ) resulting in enantiomeric products to those observed with 12 , as indicated by their identical retention times and mass spectra upon non-chiral GC-MS analysis (Fig.…”
Section: Resultssupporting
confidence: 53%
“…Purification and structural characterization of both compounds by NMR (Figs S20 – S23 and Tables S6 & S7) revealed that SsSS removes the diphosphate and forms a tertiary alcohol, ent -kolavelool ( 35 )(Soares et al, 2014), while KgTS removes the diphosphate and forms an additional carbon-carbon double bond, producing the exo -methylene containing (5 R ,8 R ,9 S ,10 R )-cleroda-3,13(16),14-triene ( 36 ), which has been previously observed (Nagashima et al, 1998). Notably, SsSS and KgTS also readily react with kolavenyl diphosphate ( 13 ) resulting in enantiomeric products to those observed with 12 , as indicated by their identical retention times and mass spectra upon non-chiral GC-MS analysis (Fig.…”
Section: Resultssupporting
confidence: 53%
“…Systematic column chromatography fractionation of hexane and CH 2 Cl 2 extracts from the aerial parts of C. pulchella lead to the isolation of the furanoid ent-clerodanes (À)-hardwikiic acid (1) (Misra et al, 1979), methyl (À)-hardwikiate (2) (Misra et al, 1979), (À)-hautriwaic acid lactone (3) (Bohlmann and Grenz, 1972;Hsü et al, 1971), methyl (À)-nidoresedate (4) (Pandey et al, 1984), methyl (À)-strictate (5) (Tandon and Rastogi, 1979;Pandey et al, 1984), together with (+)-(13E)-labd-13-ene-8,15-diol (6) (Nagashima et al, 1998;Forster et al, 1985), and (+)-isoabienol (7) (Nagashima et al, 1998;Cabrera et al, 1983). In addition, bcaryophyllene oxide (Krebs et al, 1990), sphatulenol (Tinto et al, 1992), eudesm-4(15)-en-1b,6a-diol (Sun et al, 2004), lupeoyl stearate (Razdan et al, 1996), a-amyrin and b-amyrin stearates (Mendes et al, 1999), b-sitosterol 3-O-b-D-glucoside (Ahmad et al, 2003), stigmasterol 3-O-b-D-glucoside (Ahmad et al, 2003), bsitosterol, stigmasterol and stigmastenol were also isolated from this source.…”
Section: Resultsmentioning
confidence: 99%
“…Clerodanes and labdanes with related structures are often isolated from the same organism, since it is considered that the clerodane skeleton biogenetically derives from a labdane via series of methyl and hydride shifts (Dewick, 2009). In some cases, a species can elaborate both the normal labdane-type and the ent-clerodane-type (neoclerodane) diterpenoids (Nagashima et al, 1998;Rijo et al, 2002). It is also of interest that cis and trans ent-clerodane compounds are known (Merritt and Ley, 1992) and that the stereochemistry of some furanoid ent-clerodanes has been revised (Pandey et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…cordifolia [101] , Jungermannia rotundata [102] , Jungermannia hattoriana [103] , Jungermannia infusca [104][105][106] , Jungermannia subulata (cell suspension culture) [107] , Jackiella javanica [108,109] , Pellia endiviifolia [110] , P. perrottetiana [111] , …”
Section: Diterpenoidsmentioning
confidence: 99%